Liberalism, nationalism and design reform in the Habsburg empire museums of design, industry and the applied arts - Rampley, Matthew 1966-; Prokopovych, Markian 1972-; Veszprémi, Nóra (Routledge research in art museums and exhibitions, 2020)
"Liberalism, Nationalism and Design Reform in the Habsburg Empire is a study of museums of design and applied arts in Austria-Hungary from 1864 to 1914. The Museum for Art and Industry (now the Museum of Applied Arts) as well as its design school occupies a prominent place in the study. The book also gives equal attention to museums of design and applied arts elsewhere in the Empire, including museums in Budapest, Prague and Cracow. The book is shaped by two broad concerns: the role of liberalism as a political, cultural and economic ideology motivating the museums' foundation, and their engagement with the complex dynamics and politics of imperial, national and regional identity of the late Habsburg Empire. This book will be of interest for scholars of musuem studies, design history, and European studies"--